MiR-205-5p inhibits thymic epithelial cell proliferation via FA2H-TFAP2A feedback regulation in age-associated thymus involution. (June 2020) - Gong, Bishuang; Wang, Xintong; Li, Boning; Li, Ying; Lu, Rui; Zhang, Kaizhao; Li, Bingxin; Ma, Yongjiang; Li, Yugu
Highlights: 1.miR-205−5p is highly expressed in mouse thymic epithelial cells. 2.miR-205−5p is steeply up-regulated from 1 to 9 months old TECs. 3.miR-205−5p represses TECs proliferation via targeting Fa2h. 4.Tfap2a can interact with miR-205−5p and be promoted by Fa2h. 5.miR-205−5p regulates the age-associated thymus involution by mediating Fa2h-miR-205−5p-Tfap2a feedback regulatory circuit. Abstract: Thymic epithelial cells (TECs) are essential regulators of T cell development and selection. microRNAs (miRNAs) play critical roles in regulating TECs proliferation during thymus involution. miR-205−5p is highly expressed in TECs and increases with age. However, the function and potential mechanism of miR-205−5p in TECs are not clear. miRNA expression was profiled using TECs from male and female mice at 1 and 3 months old. A total of 325 differentially expressed miRNAs (DEMs) were detected at different ages in two sexes. 24 of the DEMs had the same trend between males and females. Among them, miR-205−5p had the highest fold change. Our results showed that the expression of miR-205−5p was dramatically increased in TECs from 1 to 9 months old mice. miR-205−5p mimic inhibited TECs proliferation. Moreover, we confirmed that Fa2h was the direct target gene of miR-205−5p and FA2H was significantly decreased in TECs with increased expression of miR-205−5p. Silencing of Fa2h inhibited TECs proliferation. Furthermore, we found that the expression of Tfap2a could be promoted by FA2H and that TFAP2A could interact with miR-205−5p in TECs. Overall, miR-205−5p is an important regulator of TECs proliferation and regulates age-associated thymus involution via the miR-205−5p-FA2H-TFAP2A feedback regulatory circuit. miR-205−5p might act as a potential biomarker in TECs for age-related thymus involution.